Comparative Effectivness of Visual Feedback and Verbal Augmented Feedback for Improving Balance in Stroke Patients - Nida Chaudhary, Marium Zafar, Komal Tariq, Adeera Azam, Rashida Muneer, Hira Zafar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Stroke is a highly prevalent condition and leading cause of chronic disability in adults. Some of the important complications of stroke include complications of immobility such as pressure sores, falls and gait problems resulting from balance and coordination issues that limits person's ability to perform activities of daily living. Objectives: To compare the effectiveness of visual feedback and visual feedback combined with verbal augmented feedback for improving balance in stroke patients. Materials and Methods: A randomized clinical trial was conducted in which a sample of 30 chronic stroke patients was randomly allocated into 2 groups, control and treatment group. Group A received Visual Feedback and Group B received Visual and Verbal Feedback both. Berg Balance Scale was used to assess patients balance abilities of patients both pre and post intervention. Both groups received their respective interventions 3 times a week on alternate days for 8 weeks. Results: The data was analyzed using SPSS Version 22. Results of Paired sample T Test showed improvement in both groups over the period of 8 weeks (p <0.05). Independent sample T Test demonstrated significant improvement in Berg Balance Scale scores at 8th week follow up (p <0.05).. Significant improvement was shown in the patients who received visual feedback combined with verbal feedback. Conclusion: Visual feedback combined with verbal augmented feedback was found more effective for improving balance in stroke patients. Keywords: Stroke, Stroke Rehabilitation, Mirror Movement Therapy, Visual Feedback, Audio Feedback, Postural Balance.